Effects of a blended multimedia teaching approach on self-efficacy and skills in over-the-counter medication counselling versus a lecture-based approach: protocol for a prospective cohort study of undergraduate students from a pharmacy school in Taiwan. Issue 1 (25th January 2023) - Huang, Yen-Ming; Chan, Hsun-Yu; Wang, Yao-Hsing; Ho, Yunn-Fang
Abstract : Introduction: Addressing communication skills in pharmacy curricula is one of the effective tactics to equip future pharmacists with better skillsets for medication counselling. To achieve this, blended teaching of PowerPoint slides and videos holds great potential for undergraduate pharmacy education majors by integrating multimedia and performance feedback into instruction. This study will develop a blended teaching programme featuring didactic lectures with video-based materials to improve students' self-efficacy and skills in medication counselling. Methods and analysis: This study applies critical principles and effects outlined in multimedia learning by Richard Mayer et al to develop teaching materials and perform skill evaluation for two undergraduate cohorts (class of 2025 and 2026) enrolled in Introduction to Community Pharmacy separately in 2022 and 2023. Students will receive different teaching approaches to medication counselling. In the control cohort (ie, class of 2025), students will receive a 4-week PowerPoint slides-based instruction in communication skills. We will develop six videos illustrating common scenarios of over-the-counter (OTC) medication counselling in community pharmacies. In the intervention cohort (ie, class of 2026), students will receive a 3-week PowerPoint slides-based instruction and a week-long video-based instruction in communication skills. A pre-and-post survey will be administered to evaluate students' self-efficacy in OTC counselling. In addition, each student will be evaluated through one-on-one role-playing with standardised patients in the final to demonstrate their skills in OTC counselling. A structured checklist will be used to assess students' counselling skills. T-tests will be applied to examine differences in self-efficacy of OTC counselling. Multivariate regression analyses will determine which teaching approach better facilitates the development of self-efficacy and performance in OTC counselling. Ethics and dissemination: The Research Ethics Committee of the National Taiwan University Hospital approved this study. The findings will be shared with pharmacy educators and contribute to existing instructional methods to facilitate the competence of pharmacy students in OTC counselling.